Rational-Legal Authority and Electoral Legitimacy: Reassessing Max Weber’s Theory of Power through the 2024 Election in Bandung - Nurcahya, Yan (INDO PUBLISHING, 2025)
This study reexamines Max Weber’s concept of rational-legal authority through the lens of the 2024 election in Bandung, Indonesia. As a modern democratic mechanism, elections are the primary means by which legal-rational legitimacy is established and maintained within the state. The research explores how bureaucratic procedures, institutional transparency, and public trust interact to sustain electoral legitimacy in a local democratic context. By analyzing the administrative processes and citizen perceptions surrounding the 2024 election, the paper evaluates the extent to which Weber’s ideal type of authority aligns with the realities of Indonesia’s political system. The findings suggest that while rational-legal authority remains the dominant framework of governance, its legitimacy increasingly depends on social trust, digital transparency, and procedural fairness. Thus, the Bandung case provides insight into the evolving nature of rational-legal legitimacy in the twenty-first-century democratic state.